Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376367
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Presentation of Network Data: Text, Matrix or Diagram?

Abstract: Visualisations are commonly used to understand social, biological and other kinds of networks. Currently we do not know how to effectively present network data to people who are blind or have low-vision (BLV). We ran a controlled study with 8 BLV participants comparing four tactile representations: organic node-link diagram, grid node-link diagram, adjacency matrix and braille list. We found that the node-link representations were preferred and more effective for path following and cluster identification while… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It also requires a prebuilt 3D protein structure, which can be a difficult task for teachers and researchers. The use of note-link representation in the conversion of social network visualization from educational materials to tactile graphics was deemed the most effective way to identify the connection between two networks [50]. We also found that the small sample size and the lack of variability in the graphs may have prevented the study and results from being complete and accurate.…”
Section: Advantages and Disadvantages Of Existing Solutions In Education And Adaption Of Bvimentioning
confidence: 91%
See 3 more Smart Citations
“…It also requires a prebuilt 3D protein structure, which can be a difficult task for teachers and researchers. The use of note-link representation in the conversion of social network visualization from educational materials to tactile graphics was deemed the most effective way to identify the connection between two networks [50]. We also found that the small sample size and the lack of variability in the graphs may have prevented the study and results from being complete and accurate.…”
Section: Advantages and Disadvantages Of Existing Solutions In Education And Adaption Of Bvimentioning
confidence: 91%
“…To the best of our knowledge, one of the current problems confronting BVI individuals is the lack of teaching materials in the field of education, especially in STEM subjects. Several primary studies, such as [11,49,50,56], presented different approaches as a solution to this problem. Giovanni and Morash [11] introduced a machine vision-based tactile graphics helper (TGH), which followed the fingers of blind students as they investigated tactile graphics and enabled them to obtain refined audio messages regarding the tactile graphics without sighted assistance.…”
Section: Tactile Graphics For Stem Subjects and Braille Booksmentioning
confidence: 99%
See 2 more Smart Citations
“…In tactile graphics, heavy guidelines (e.g., grids) can hamper the efficient perception of data, as with overwhelming content and ambiguous textures that are used in place of color [EW17b, EW17a, YMB ∗ 20]. Grasping a chart's orientation is also crucial for a visually impaired user to successfully understand the visualization [EW17b].…”
Section: Design Spacementioning
confidence: 99%